Economic and social motives of using geography-related information and communication technologies: a Japanese-Hungarian comparative study - Akos Jakobi (European Regional Science Association (ERSA), 2012)
Theoretical as well as practical experiences of analyses confirmed that spatial processes of the diffusion of information and communication (ICT) technologies largely influenced the economy and society of the 21st century. In the last couple of years, a new motive of ICT-based inequalities seemed to appear that could have been connected to the usage of geographical information, since the progression of information technologies influenced also the diffusion of information having geographical content. Recently, significant growth is shown by certain circles of industries and services attached to information technology tools, which provide geoinformation – namely information made up with spatial, geographical substance – to users in a direct or indirect way. The "geoinformation business", therefore, gained an increasing share in information economy. As an affect of the technological change many examples can be cited from location aware smartphones to map services of the Internet, which represent how people's opinion on the everyday role of geographical information could have altered. Indirectly geographical information systems (GIS) slowly and invisibly got diffused in everyday life, just think on the spread of GIS-based web mapping, Google Earth and other Digital Earth solutions, GPS-related activities, location based services or other geographical extensions of virtual reality and augmented reality in cyberspace. Although the spread of innovations associated with geoinformation services was quite fast and global sized, it seems that market possibilities of this sector is largely dependent on location, not just because of different business environments, but also due to diverse attitude and intention of people of adapting new innovations. Present research was aiming to test the above-mentioned hypothesis by comparing Japan, an advanced country of information technologies, and Hungary, a member state of the EU with different backgrounds and opportunities of ICT development. In the last couple of months as a cooperation between the University of Tokyo, the Ritsumeikan University in Kyoto and the Eötvös Loránd University in Budapest, questionnaire surveys were made to compare how Japanese and Hungarian people are using map-information based personal applications and what is their relation to geoinformation services. According to the results different technological background or different level of development is not the only explanatory factor of the spread of geoinformation services, the local circumstances seems to play an important role as well.
Keywords: L86; L96; O18; O33; O57; R00; 330; ICT; information society; information economy; GIS; geographic information; Japan; Hungary; geoinformation business